Ответ:
[tex]( \frac{1}{3} ) ^{ - 3} - ( - \frac{5}{7} ) ^ {0} + ( \frac{1}{2} ) ^{2} \div 2 = {3}^{3} - 1 + \frac{1}{4} \times \frac{1}{2} = 27 - 1 + \frac{1}{8} = 26 \frac{1}{8} [/tex]
Объяснение:
в деситичной форме : 26,125
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]( \frac{1}{3} ) ^{ - 3} - ( - \frac{5}{7} ) ^ {0} + ( \frac{1}{2} ) ^{2} \div 2 = {3}^{3} - 1 + \frac{1}{4} \times \frac{1}{2} = 27 - 1 + \frac{1}{8} = 26 \frac{1}{8} [/tex]
Объяснение:
в деситичной форме : 26,125